Hadith #2241 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Isa bin al-Mukhtar عيسى بن المختار بن عبد الله بن عيسى (Sunan Abi Dawud)
I embraced Islam while I had eight wives. So I mentioned it to the Prophet (ﷺ). The Prophet (said) said: Select four of them. Abu Dawud said: This tradition has also been narrated to us by Ahmad b. Ibrahim from Hushaim. He said: Qais b. al-Harith instead of al-Harith b. Qais. Ahmad b. Ibrahim said: This is correct, i.e. Qais b. al-Harith.
Grade: Sahih